Well, you have hepatic metastases: Use of technical language by medical students in simulated patient interviews. Issue 3 (March 2015) - Bourquin, Céline; Stiefel, Friedrich; Mast, Marianne Schmid; Bonvin, Raphael; Berney, Alexandre
Abstract Objective This research explored medical students' use and perception of technical language in a practical training setting to enhance skills in breaking bad news in oncology. Methods Terms potentially confusing to laypeople were selected from 108 videotaped interviews conducted in an undergraduate Communication Skills Training. A subset of these terms was included in a questionnaire completed by students (N = 111) with the aim of gaining insight into their perceptions of different speech registers and of patient understanding. Excerpts of interviews were analyzed qualitatively to investigate students' communication strategies with respect to these technical terms. Results Fewer than half of the terms were clarified. Students checked for simulated patients' understanding of the terms palliative and metastasis/to metastasize in 22–23% of the interviews. The term ambulatory was spontaneously explained in 75% of the interviews, hepatic and metastasis/to metastasize in 22–24%. Most provided explanations were in plain language; metastasis/to metastasize and ganglion/ganglionic were among terms most frequently explained in technical language. Conclusion A significant number of terms potentially unfamiliar and confusing to patients remained unclarified in training interviews conducted by senior medical students, even when they perceived the terms as technical. Practice implications This exploration may offer important insights for improving future physicians' skills.